Simulation and Analysis the Attenuation Effect of Atmospheric Layers on a Laser Beam Within the Visible Range - Al-Aish, Thair Abdulkareem Khalil; Mohammed Kamal Saleh , (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Abstract: The power and the size of the final spot of the laser beam reaching the target are very important requirements in most of the laser applications and fields such as medical, military, and scientific, so studying laser propagation in the atmosphere is a very important topic. The propagation of the laser beam through the atmosphere is subject to several attenuation processes that deplete the power and expand the beam. Through the simulation results of the free electron laser within the visible region of the electromagnetic spectrum (400-700nm), it was found that the attenuation increases with decreasing wavelength. Laser propagation in the presence of rain and snow leads to a very large loss of power compared to propagation in normal weather conditions free of rain and snow. Atmosphere turbulence depends largely on changes in temperature, so the turbulence decreases with altitude from sea level, which makes laser work at high altitudes, such as the stratosphere, a good option with better results.